2016
DOI: 10.1111/odi.12542
|View full text |Cite
|
Sign up to set email alerts
|

The effects of customised brainwave music on orofacial pain induced by orthodontic tooth movement

Abstract: Brainwave music is effective in controlling orthodontic pain, possibly via restoring functional connectivity and brain regularity influenced by pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 41 publications
2
31
1
3
Order By: Relevance
“…Cognitive behavioral therapy was a method identified as effective in controlling orthodontic pain by Sawada et al, 49 Wang et al, 50 , 51 and Zheng et al 52 The latter also reported positive results with music therapy, muscle relaxation therapy, and suggestion therapy. The positive effect of music on orthodontic pain reduction was also reported by Huang et al 53 and Xu et al 54…”
Section: Resultssupporting
confidence: 71%
“…Cognitive behavioral therapy was a method identified as effective in controlling orthodontic pain by Sawada et al, 49 Wang et al, 50 , 51 and Zheng et al 52 The latter also reported positive results with music therapy, muscle relaxation therapy, and suggestion therapy. The positive effect of music on orthodontic pain reduction was also reported by Huang et al 53 and Xu et al 54…”
Section: Resultssupporting
confidence: 71%
“…We also used real EEG data with different references to generate brainwave music. The data was recorded in an orthodontic pain control experiment (Huang et al, 2016 ). This study was approved by the Ethics Committee of the West China Hospital of Stomatology.…”
Section: Methodsmentioning
confidence: 99%
“…This study was approved by Ethical Committee of West China Hospital of Stomatology, and informed consents were signed by all the participants. Sample size was estimated based on the difference in mean of 10.41 by a similar study (Ileri et al , ) and the standard deviation of 13.86 by our recent study (Huang et al , ). With a type I of 0.05 and a power of 80%, the sample size was calculated to be 29.…”
Section: Methodsmentioning
confidence: 99%